Effective Strategies for Improving Vocabulary Proficiency among Upper Secondary Level Students - AR. Mehthaff Banu; MJF Sujani; MB Nowzath; MR. Rishad Muhammed (Elementaria: Journal of Educational Research, 2024)
The study aimed to enhance vocabulary proficiency among upper secondary students in English literature at Al Mazhar Girls’ High School, Nintavur. The objectives were to identify effective teaching methods for vocabulary acquisition, evaluate students’ attitudes toward literature-based vocabulary learning, and recommend integrating literature into the curriculum. A mixed methods approach was used, combining quantitative data from pre-tests, mid-tests, and post-tests with qualitative insights from structured questionnaires and observations. Out of 35 GCE(O/L) students who took the pre-test, 20 were selected for the study. Data analysis in MS Excel revealed significant improvements in students' vocabulary skills following the intervention. Strategies such as song-based learning, vocabulary games, and language boards proved highly effective. Pre-test and post-test comparisons showed notable progress, while qualitative data reflected positive student feedback and engagement. The study recommends integrating literature-based instruction and interactive methods, such as songs and games, into the curriculum to enhance vocabulary acquisition. These strategies not only improved learning outcomes but also increased students’ interest and motivation in acquiring new vocabulary.